Laryngology Quality of Life Questionnaire Associations: Towards Reducing Survey Burden. (9th September 2020) - Young, VyVy N.; Jordan, Kristiana M.; Schneider, Sarah L.; Lazar, Ann; Dwyer, Christopher D.; Rosen, Clark A.
Abstract : Objectives: Outcomes in laryngology focus primarily on patient reported outcome measures (PROMs). The increasing number of questionnaires may lead to survey fatigue. We sought to determine the relationship between the newest questionnaire, Laryngopharyngeal Universal Measure of Perceived Sensation (LUMP), and other laryngology PROMs. Study Design: Cross‐sectional study. Methods: Patients undergoing laryngology multidisciplinary evaluation prospectively completed laryngology questionnaires. Average summed scores between standard laryngology PROMs (ie, VHI‐10, RSI, DI, CSI, EAT‐10) and LUMP were compared. Expert consensus panel identified the most clinically relevant statements which were then compared to LUMP summed scores, in increasingly additive fashion. Results: Four hundred eighty patients (259 female) were assessed. Average age was 57.1 ± 17.7 years. Intraclass correlation coefficient (ICC) for each PROM in comparison to LUMP ranged from moderate to poor correlation: 0.64 (RSI), 0.55 (EAT‐10), 0.50 (DI), 0.48 (CSI), and 0.34 (VHI‐10). ICC for combinations of the five most clinically relevant individual items ranged from 0.29–0.53. Conclusions: Patients with self‐reported globus had statistically significantly higher scores across all PROMs. RSI had moderate correlation with LUMP, and the five selected expert consensus items demonstrated weaker correlation. While RSI may serve as a moderately selective clinical proxy for the LUMP questionnaire, LUMP remains a validated tool with increased specificity for quantification of globus which may be especially important in the research setting. There is continued question about the need for multiple laryngologic PROMs to evaluate patient complaints, and survey reduction remains an area of interest to decrease respondent fatigue, optimize patient care, and quantify interventional success. Level of Evidence: 4 Laryngoscope, 131:1561–1565, 2021